Penyelesaian Perkara Pidana Melalui Mekanisme Mediasi - Hatta, Muhammad (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2018)
In the Indonesian legal aspect, mediation can be applied to all civil cases, even before the judge checks the lawsuit in court, the judge must direct the disputing parties to take part in the mediation session. On the contrary, mediation cannot be applied to criminal cases because it is not regulated in criminal procedural law. In Islamic criminal law, cases that can be resolved through mediation are qisas, diyat and ta`zir. Qisas and diyat known as penalties that have been determined by the nash which violate human rights (individuals) so that victims or their heirs can forgive the perpetrators. To get forgiveness from the victim's heirs, the perpetrator can ask someone, organization or government as a mediator to consult so that the victim's heirs will forgive the perpetrator's mistake. Furthermore, ta’zir is fully handed over to government policy (ulil amri), including the material law and procedural law. The government can make regulations that adopt mediation mechanisms to resolve conflicts that occur in the community.